Handbook of archaeological sciences - Armitage, Ruth Ann; Makarewicz, Cheryl; Pollard, A. M. (Wiley, 2023)
The Handbook of Archaeological Sciences brings together all branches of archaeological science in one place. The book is organised under 10 broad headings: dating, quaternary palaeoenvironments, human bioarchaeology, biomolecular archaeology, archaeogenetics, biological resource exploitation, inorganic resource exploitation, archaeological prospection, conservation science in the archaeological context and statistical and computer applications. The contributors, who are all well-known in their own areas of expertise, bring together in each chapter the basic science and the relevance of this science to the overall goal of archaeology - understanding humans in the past. This book is an invaluable source of reference for those interested in archaeology, anthropology, quaternary studies, geography, palaeoecology, computing, biology, chemistry and physics, those involved in commercial and local authority field archaeology units, museums and archaeological organisations"--